2006
DOI: 10.1007/s00464-005-0855-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic-assisted laparoscopic low anterior resection with total mesorectal excision for rectal cancer

Abstract: Robotic-assisted laparoscopic low anterior resection for rectal cancer is feasible in experienced hands. This technique may facilitate minimally invasive radical rectal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
251
2
9

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 346 publications
(278 citation statements)
references
References 11 publications
6
251
2
9
Order By: Relevance
“…Early experiences with different robotic-assisted colorectal procedures such as colectomies (Rawlings et al, 2006;D'Annibale et al, 2004), rectopexy (Munz et al, 2004) and anterior resections (D'Annibale et al, 2004 are described in recent literature including our previous early report of robotic-assisted TMEs (Pigazzi et al, 2006). These studies found no difference in specimen length, number of lymph nodes retrieved, estimated blood loss, recovery of bowel function or hospital stay between laparoscopic and robotic colorectal resections.…”
Section: Discussionmentioning
confidence: 99%
“…Early experiences with different robotic-assisted colorectal procedures such as colectomies (Rawlings et al, 2006;D'Annibale et al, 2004), rectopexy (Munz et al, 2004) and anterior resections (D'Annibale et al, 2004 are described in recent literature including our previous early report of robotic-assisted TMEs (Pigazzi et al, 2006). These studies found no difference in specimen length, number of lymph nodes retrieved, estimated blood loss, recovery of bowel function or hospital stay between laparoscopic and robotic colorectal resections.…”
Section: Discussionmentioning
confidence: 99%
“…в 2006 г. [20]. Он сравнил непосредственные результаты роботи-ческой тотальной мезоректумэктомии с тра-диционной лапароскопической методикой.…”
Section: применение роботической хирургии в современной колопроктологииunclassified
“…В 2008 г. Pigazzi et al [20] публикуют ре-зультаты первых 6 роботических тотальных мезоректумэктомий и сравнивают их с тради-ционными лапароскопическими. Они также докладывают о выполнении 39 операций по www.malignanttumors.org Journal of Malignant tumours поводу рака прямой кишки [23].…”
Section: применение роботической хирургии в современной колопроктологииunclassified
See 2 more Smart Citations